Anesthesia management for total robotic liver transplantation - Duarte, Ana (2024)
Robotic liver transplantation represents a cutting-edge technique that may surpass traditional open surgery. Nonetheless, it introduces unique anesthetic challenges, including extended pneumoperitoneum, restricted patient access, and a risk of undetected blood loss. This article describes an anesthetic approach and patient outcomes for the first four total robotic liver transplants performed at a tertiary university hospital in Portugal, along with inaugural procedures of their kind in Europe. We retrospectively analyzed surgical and anesthetic data from four patients who underwent total robotic liver transplantation from February to April 2024. Data encompassed clinical profile, preoperative assessment, surgical and anesthesia details, postoperative course, and outcomes. Patients' age ranged from 51 to 69 years. Their cirrhosis was primarily due to alcohol use, hepatitis C virus infection, hepatocellular carcinoma, or nonalcoholic steatohepatitis. General anesthesia was administered. Hemodynamic monitoring and goal-directed fluid therapy were conducted using a PiCCO system. Blood loss varied from 1,000 to 5,000 mL. Blood products were transfused as needed. All donor livers underwent hypothermic oxygenated machine perfusion before transplantation. After surgery, two patients were immediately extubated, while two required extended ventilation. Hospital stays ranged from 10 to 40 days. The 30-day survival rate was 100%. This initial case series affirmed the feasibility and safety of total robotic liver transplantation for carefully selected patients, yielding favorable short-term results. Anesthetic management can rely on proactive strategies, acute situational awareness, and effective multidisciplinary collaboration.